Potensi Culex quinquefasciatus sebagai Vektor Filariasis dan Kondisi Lingkungan di Kota Pekalongan: The Potential of Culex quinquefasciatus as Lymphatic Filariasis Vector in Pekalongan City - Nurjazuli; Dewanti, Nikie Astorina Yunita (Aspirator, 2021)
Abstract. Pekalongan City was still an endemic area of Lymphatic Filariasis (LF). Twice cycles of Mass Drug Administration (MDA) had been implemented, but the Microfilaria rate (Mf rate) was still more than 1%. This observational research aimed to study the potential of Culex quinquefasciatus as a vector of LF in Pekalongan City. A Cross-sectional design was chosen as an approach in compiling information related to environmental factors and mosquitoes. The population of this research was houses located in Jenggot and Kertoharjo village with thirty-one houses, located around filariasis cases, purposively selected as samples. Variables studied in this research were environmental factors and mosquito vectors. Data collection using observation, and laboratory examination through mosquito dissection. Data would be analyzed descriptively. This study found that there were 8 Cx. quinquefasciatus tested positive L3 filarial worm (infective rate 4.39%). There were 74.2% of houses had mosquitoes’ breeding sites around them. The breeding sites were found at domestic waste disposal, drainage in front of the house, and infiltration well for liquid waste. As much as 86.2% of the breeding sites contained mosquito larvae. This research concluded that Cx. quinquefasciatus was confirmed positive filaria worm thus establish as mosquito vector for Lymphatic Filariasis in Pekalongan City. The breeding sites related to the mosquito development were small water bodies, drainage in front of and around the house. Abstrak. Kota Pekalongan merupakan satu daerah endemis filariasis di Jawa Tengah (Mf rate >1%). Pemberian Obat Pencegahan Massal (POPM) telah dilaksanakan sebanyak 2 siklus, namun kasus filariasis baru masih ditemukan. Penelitian ini bertujuan untuk mengkaji potensi nyamuk Culex quinquefasciatus sebagai vektor filariasis di Kota Pekalongan. Penelitian observasi dengan desain cross-sectional ini berlokasi di Kelurahan Jenggot dan Kertoharjo. Sampel penelitian diambil secara puposive sebanyak 31 rumah yang ada di sekitar penderita filariasis. Variabel yang dikaji dalam penelitian ini adalah faktor lingkungan dan nyamuk yang diduga sebagai vektor filariasis. Penangkapan nyamuk dilakukan dengan menggunakan aspirator yang dilakukan pada pagi hari. Nyamuk yang tertangkap dilakukan pembedahan (dissesction). Penelitian ini menemukan sebanyak 8 ekor nyamuk Culex quinquefasciatus positif cacing filaria L3 (infective rate 4,39%) dan sebanyak 74,2% di sekitar rumah responden terdapat genangan air berupa buangan limbah rumah tangga, saluran air di depan rumah, dan sumur resapan yang tidak tertutup. Dari sejumlah genangan air tersebut, 86,2% diantaranya terdapat jentik nyamuk. Penelitian ini menyimpulkan bahwa Cx. quinquefasciatus terkonfimasi sebagai vektor filariasis. Kondisi lingkungan berupa genangan air di sekitar rumah menjadi tempat perindukan nyamuk.